Inhibitorentwicklung nach früher hoher Exposition und Hirnblutung - Haubold, K.; Moorthi, C.; Bade, A.; Niekrens, C.; Auerswald, G. (Hämostaseologie, 2010)
Severe haemophilia A was diagnosed postpartum in a newborn. The mother was known as a conductor (intron 22 inversion) and an uncle had a persistently high titer inhibitor after failed ITI.Due to a cephalhaematoma, a high-dose pdFVIII substitution was given within the first days after birth. At the age of six month a severe cerebral haemorrhage occurred, making a high-dose pdFVIII substitution and neurosurgical intervention necessary. Several days later a porth-a-cath-system was implanted. The development of a high titer inhibitor occured six days later, an ITI was started according to the Bonn Protocol. Initially rFVIIa was given in addition to the pdFVIII substitution. Seven days after the beginning of treatment the inhibitor was no longer detectable. At monthly intervals the FVIII dosage was reduced until the dosage complied with a prophylaxis in severe haemophilia A.The duration of the ITI was nine months. A total of 30 mg rFVIIa and 276 000 IU pdFVIII were used; costs in total: 280 173.60 Euro.
Keywords: Inhibitor development; calculation of usage and costs; immunotolerance therapy